Adaptive Virtual Inertia Control for Combined Heat Pump and Biogas Engine Generator System: An Alternative Solution for Grid-Level Energy Storage - Jonggrist Jongudomkarn; Pirat Khunkitti; Apirat Siritaratiwat (IEEE Access)
The combined heat-pump and biogas engine generator system (CHBS) serves as an alternative solution to address fluctuations in renewable generation output, offering several notable advantages such as a straightforward design that integrates a heat pump and thermal energy storage (TES) into an existing biogas plant to achieve functionality equivalent to an Energy Storage System (ESS) at cost-effective resource utilization compared to the Battery-based energy storage system. This paper introduces an adaptive control-based approach tailored for the CHBS system, designed to generate virtual inertia for frequency regulation while considering the TES’s State of Charge (SOC). The controller comprises two main loops: one for the biogas generator system and another for the heat pump. Unlike the conventional virtual inertia approach, the controller optimizes virtual inertia parameters to enhance frequency control performance by optimizing ESS charge or discharge within normal operating ranges while adjusting the parameters to minimize the power exchange rate as the TES charging state nears operational limits, ensuring that the power exchange never exceeds the available capacity of the TES. The equivalent capability of the proposed system is validated numerically by comparing it with a Battery Energy Storage System (BESS)-based system under practical conditions involving Renewable Energy Sources (RES) and fluctuating loads. The results demonstrate that the CHBS, utilizing the proposed adaptive control approach, achieves effective microgrid frequency regulation comparable to a BESS-based VI system while efficiently managing the TES’s SOC.